Degree of Pulmonary Hypertension in Patients of COPD Attending a Tertiary Care Hospital - Shaik, Afshan Ali; Lawande, Durga (International Journal of Innovative Research in Medical Science, 2021)
Introduction: Chronic obstructive pulmonary disease (COPD) is a major cause of morbidity and mortality in India. The development of pulmonary hypertension (PH) in COPD adversely affects survival and exercise capacity and is associated with an increased risk of severe acute exacerbation. Aims and Objectives: Present study aimed to describe the distribution of echocardiographically assessed pulmonary artery systolic pressure in the COPD patients attending pulmonary medicine OPD, to estimate the proportion of PH among such patients and to identify associated factors. Methodology: This Cross sectional study was done on 145 patients of COPD fulfilling the inclusion criteria were included in this study. These patients were evaluated for the presence of PH using chest X-ray, 2D-Echocrdiography and electrocardiogram. Results: Pulmonary hypertension was present in 17 (29.8%) patients with moderate, 36 (60%) with severe and 18 (72%) with very severe COPD. Mild PH was seen in 52(73%), moderate in 11(15.4%) and severe in 8(11.2%) patients. Patient exposed to both smoking and biomass fuel smoke had more frequent occurrence of PH (56.8%) as compared to exposure to single risk factor of either tobacco smoke (47.1%) or biomass fuel (52.4%). Thus overall proportion of PH among reported cases of COPD patients was 48.6% in our study. Conclusion: With the increase in severity of COPD the proportion of PH rises. This study emphasizes the early detection of COPD and the importance of screening for PH through clinical assessment and non- invasive techniques 2-D Echocardiography.